A educação e o Milagre econômico do Rio Han na Coreia do Sul (1961-1990) - Francez, Pedro Antonio Saraiva de Carvalho Pereira (2021)
This study has the emphasis on elucidating the Korean economic miracle, called the Miracle of the Han River from 1960 to 1990. Understanding and analyzing Korean history is necessary to better understand the proposed fact. The reflection of the Japanese Domination (1910-1945) over the Korean peninsula brought extremely undesirable social consequences for the population, such as illiteracy, deprivation of liberties, student backwardness, in addition to persecutions and deaths. As a reflection of the defeat in World War II (1940- 1945), the Japanese lost control of the Korean peninsula. Regardless of, just five years after Korea was freed from the atrocities committed by Japan, an ideological civil war called the Korean War (1950-1953) took place, which killed about five million people and divided the country, giving rise to North Korea and South Korea, target of this study. Totally devastated socially, culturally, politically and economically, the South Koreans had an arduous mission to rebuild the country. Plagued by hunger, unemployment and illiteracy, through long years of massive investment in education, they achieved a long-term project that, after two decades, already showed the change in the South Korean paradigm, from a destroyed and bankrupt nation to a prosperous and surplus country. It is also clear that the decentralization of education in large urban centers has helped the development and urbanization of rural areas, minimizing the damage from the rural exodus and creating opportunities in the countryside.